Perubahan Sosial Ekonomi Buruh Perempuan PTPN Vii Cinta Manis pada Masa Pandemi Covid-19 - Ersyah Hairunisah Suhada; Sriati; Zulfikri Suleman (Syntax Literate, 2023)
PT Perkebunan Nusantara VII Cinta Manis is a large-scale sugarcane plantation and has many workers, including women. Women laborers who work at PTPN VII Cinta Manis are included in vulnerable communities because they cannot get out of the poverty cycle they experience. This is reinforced by the covid-19 pandemic which has worsened the socio-economic situation of women workers. The purpose of this study is to explain the socio-economic changes of female laborers during the Covid-19 pandemic. The method used in this research is qualitative with a case study research strategy. The results of this study are that women laborers experienced significant changes during the Covid-19 pandemic from changes in thinking, changes in attitudes and changes in terms of interactions and activities. The strategies carried out also vary from utilizing skills, selling at home and social media to catfish farming to survive during the pandemic.